The Rheumatoid Arthritis Quality of Life (RAQoL) for Indonesia: Translation and Pilot Test - Khoirunnisa S.M.; Perwitasari D.A (INSIST, 2017)
Abstract— The primary objective of this research were to produce and evaluate the official Indonesian language version of the Rheumatoid Arthritis Quality of Life instrument (RAQoL). The UK RAQoL was translated into Indonesian by a forward-backward translation. A separate lay panel was conducted to consider the appropriateness and comprehensibility of the items in Indonesian. The translated version of the RAQoL was pilot tested to determine whether the questionnaire RAQoL could be well understood and well accepted. Pilot test was conducted by interviews with 20 subjects, which 10 healthy Indonesia people and 10 rheumatoid arthritis patients who were recruited from X hospital in Yogyakarta, Indonesia.  Items on the two response format questionnaire used in pilot study were scored one for a ‘yes’ response and zero for a ‘no’ response. The individual total item scores with a high score indicating poor QoL. Few difficulties arose in the translation process and the new language version was well received by the lay panel and field-test participants. Statistical analysis was conducted to determine the difference of completion time between healthy subjects and RA patients, and the total score of the questionnaire answers between healthy subjects and patients. The average total score of responses to questionnaire on the healthy subject and patients by T test was significantly different (p < 0.05). The official Indonesian RAQoL was well received by RA patients. The psychometric quality of the translated questionnaire means that it is suitable for validity and reliability of the questionnaire towards patients with RA.Keywords—Rheumatoid Arthritis, questionnaire, RAQoL, translation, pilot test